THE CHARACTERIZATION OF DIDACTIC SPEECH OF A BIOLOGY TEACHER AND HIS INFLUENCE IN THE MOTIVATION OF STUDENTS FOR BIOLOGY - Lorena Bejarano Beltrán (Bio-grafía, 2016)
The Pedagogic practice is the staging of knowledge for consideration and recognition of acquired understanding in the academic and personal level that took place in the Commercial Technical School Manuela Beltran, showing that students present lack of motivation to learn Biology , which is expressed in the limited relationship between reality, scientific concepts together with the technical language. The experiments and innovation are left aside. This is why there is a question in relation to the didactic speech and motivation of seventh and eighth grade students towards Biology. In this way the didactic speech of the teacher has been characterized to allow the identification of elements that facilitate the teaching in terms of motivation. In the same way the space for recognizing the factors that generate in the students pleasure for the subject given, in which the games, the participation and the experiments were aspects that they will like to have in their classes. The present investigation had and interpretative paradigm and a qualitative perspective, such instruments like the nonparticipant observation,six recordings of Biology classes making analyses of information units where categories emerged, as well as a questionnaire applied to 25 students.